170 THE EFFECT OF HYPERBARIC OXYGEN ON ENDOTHELIAL NITRIC OXIDE SYNTHASE EXPRESSION IN ISCHEMIA-REPERFUSION INJURY. Issue 1 (1st January 2007) - Bellister, S. A.; Khiabani, K. T.; Stephenson, L. L.; Fang, X. H.; Wang, W. Z.; Zamboni, W. A.
Abstract : Introduction: The beneficial effects of hyperbaric oxygen (HBO) in the amelioration of ischemia-reperfusion (IR) injury have been shown to occur through a nitric oxide-dependent mechanism. Previous work has shown an early increase in eNOS activity caused by HBO. There is also a late up-regulation of eNOS mRNA. The purpose of this experiment is to determine if there is an increase in eNOS protein following HBO treatment. α2-Antiplasmin (α2-antiplasmin) was administered to determine the source of eNOS. Methods: The gracilis muscle flap was raised in 40 male Wistar rats ( n = 10/group). Rats were divided into four groups: a nonischemic control, IR, IR + HBO (100% O2 at 2.5 ATA) and an IR + HBO + α2-antiplasmin group each with an n = 10. Ischemia consisted of 4 hours of global ischemia on the gracilis muscle flap. The α2-antiplasmin was administered by direct continuous infusion into the gracilis muscle prior to HBO. The HBO treatment consisted 100% O2 at 2.5 ATA during the last 90 minutes of ischemia. The gracilis muscle and pulmonary vasculature were harvested 30 minutes after reperfusion, weighed, and flash frozen in liquid nitrogen. A Bradford assay was performed to determine the total protein quantity. The quantity of eNOS protein was measured using Western immunoblotting. Results: IR did not significantly increase eNOS protein compared with the nonischemic control (35.6 ± 1.3 vs 38.6 ± 1.7 ng). HBO did not change the level of eNOS protein in skeletal muscle (38.8 ± 2.0 ng). In addition, the blockade of the plasmin/eNOS cascade had no effect on the level of eNOS protein (35.8 ± 2.7 ng). Discussions: These results offer evidence that the immediate increase in eNOS activity seen in HBO treated IR injury is not due to an increase in eNOS protein. Instead, it may be related to an increase in VEGF protein or mechanotransduction of the VEGFR2 caused by the sheer stress of reperfusion.